STRATEGI PELIPUTAN BENCANA GEMPA MAMUJU DI TVRI SULAWESI BARAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study shows that the process of reporting during a disaster is not much different from ordinary reporting, the difference being the field conditions, the condition of the sources, and the condition of the journalists themselves, in the sense that at the time of reporting the journalists must pay attention to the condition of the body in a healthy and stable condition when they want to do disaster coverage. The strategies used by TVRI journalists in West Sulawesi are (1) keeping emotions in check, (2) looking for competent sources, (3) paying attention to the field situation, (4) using language that is easily understood by sources, (5) quickly determining the theme of the news. Regarding the supporting factors for West Sulawesi TVRI journalists during disaster coverage, namely (1) communication tools (2) building good relations, while the inhibiting factors are (1) no network and electricity, (2) field conditions, (3) difficulty in finding sources.